2016
DOI: 10.1590/abd1806-4841.20165013
|View full text |Cite
|
Sign up to set email alerts
|

Bromoderma in an infant

Abstract: Bromoderma is a cutaneous eruption caused by the absorption of bromide. Clinical manifestations include acneiform and vegetative lesions. We report the case of an infant with bromoderma caused by the use of syrup for abdominal colic containing calcium bromide. The lesions regressed after discontinuation of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Local excision with sufficient surgical margins, or Mohs surgery, is usually sufficient and superior to amputation of the distal phalanx. 3 In the patient described, the atypical herpetic whitlow probably developed after autoinoculation from the nasal lesions. Common entities with atypical presentations should always be included in the differential diagnosis of disorders in immunocompromised patients.…”
mentioning
confidence: 90%
“…Local excision with sufficient surgical margins, or Mohs surgery, is usually sufficient and superior to amputation of the distal phalanx. 3 In the patient described, the atypical herpetic whitlow probably developed after autoinoculation from the nasal lesions. Common entities with atypical presentations should always be included in the differential diagnosis of disorders in immunocompromised patients.…”
mentioning
confidence: 90%
“…Since 1948 at least 40 cases have been reported in the literature, 12 of which in the childhood (Hoefel, Camozzato, Hagemann, Rhoden, & Kiszewski, 2016;Roosel et al, 1981). Since 1948 at least 40 cases have been reported in the literature, 12 of which in the childhood (Hoefel, Camozzato, Hagemann, Rhoden, & Kiszewski, 2016;Roosel et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Bromoderma is a rare cutaneous hypersensitivity reaction to bromide exposure. Since 1948 at least 40 cases have been reported in the literature, 12 of which in the childhood (Hoefel, Camozzato, Hagemann, Rhoden, & Kiszewski, 2016;Roosel et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Iododerma is well described in the literature in patients administered iodinated contrast media for imaging, especially in those with renal failure due to impaired clearance . Bromoderma has recently been described in infants after antiepileptic therapy and following calcium bromide for abdominal colic . Verrucous‐type lesions are not commonly described …”
Section: Discussionmentioning
confidence: 99%
“…3 Bromoderma has recently been described in infants after antiepileptic therapy and following calcium bromide for abdominal colic. 4,5 Verrucous-type lesions are not commonly described. 6 When we checked our patient's medication, we found that he was using two inhalers containing halogens: an ipratropium bromide inhaler (containing one bromide ion in the chemical structure) and a salmeterol/fluticasone combination inhaler (containing three fluoride ions), which helped to confirm our diagnosis.…”
Section: Discussionmentioning
confidence: 99%